KIND SPEECH IN THE PROPHETIC SUNNAH AND ITS RELEVANCE TO COMMUNICATION ETHICS ON SOCIAL MEDIA: A HADITH ANALYSIS FROM THE NARRATIONS OF AL-BUKHARI AND MUSLIM - Syahviva, Risma; Hasanah, Uswatun; Ghazali, Muhammad (Jurnal Studi Hadis Nusantara, 2025)
Communication is essential in social interaction. Therefore, even a brief lack of communication can lead to discomfort. This is inseparable from the fact that humans are social creatures. However, the most important aspect is the application of ethics in communication. Something that could be conveyed well may become something negative if it is not communicated with proper ethics. This study analyses the ethics of communicating on social media by reviewing the concept of ‘kind speech’ from the perspective of Hadith narrated by Imam Bukhari, No. 6024 and Imam Muslim, No. 47. This study aims to examine how the principles contained in the Hadith regarding ‘kind speech’ can be applied in online interactions. This research is based on a qualitative method using relevant Hadith texts with a focus on their interpretation and application in the context of digital communication. The results show that the meaning of ‘kind speech’ in the hadith narrated by Al-Bukhari and Muslim has significant relevance to communication ethics on social media. Social media users should always try to use kind speech and avoid bad words on social media. Thus, social media users can maintain harmony in their communication on social media.